Novel use of native gellan gum - YUMIKO YAMADA; HIROO NAKAMURA; KAZURO UCHIDA; TOMOAKI SAKANASHI; MIE KAKO; TOSHINAGA TAMIYA; YOSHIKO NISHINO; GENYO NAKANO; TADANOBU NISHIKAWA; YOSHIKI NAKAO; NORIFUMI ADACHI; YUKIKO KOHARA; et al. (1998)
The invention provides a native gellan gum-containing composition, and particularly based on the multifunctionality thereof, provides freeze/thaw-resistant gel compositions and dehydrated gels and jellies available therefrom, rice cake-like gels and rice cake substitutes, copy foods, cold retention compositions and cooling agents. The invention further provides the use of the above composition as additives for the expression of unique functions, for example a dispersion stabilizer, an additive for thickened compositions, a heat resistance-imparting agent, a syneresis inhibitor, a foam stabilizer, and a food palatability/body-improving agent.